Cognitive, Parent and Teacher Rating Measures of Executive Functioning: Shared and Unique Influences on School Achievement - Dekker, Marielle C.; Ziermans, Tim B.; Spruijt, Andrea M.; Swaab, Hanna (Frontiers in Psychology, 2017)
Very little is known about the relative influence of cognitive performance-based executive functioning (EF) measures and behavioural EF ratings in explaining differences in children’s school achievement. This study examined the shared and unique influence of these different EF measures on math and spelling outcome for a sample of 84 first and second graders. Parents and teachers completed the Behaviour Rating Inventory of Executive Function (BRIEF), and children were tested with computer-based performance tests from the Amsterdam Neuropsychological Tasks (ANT). Mixed-model hierarchical regression analyses, including intelligence level and age, showed that cognitive performance and teacher’s ratings of working memory and shifting concurrently explained differences in spelling. However, teacher’s behavioural EF ratings did not explain any additional variance in math outcome above cognitive EF performance. Parent’s behavioural EF ratings did not add any unique information for either outcome measure. This study provides support for the ecological validity of performance- and teacher rating-based EF measures, and shows that both measures could have a complementary role in identifying EF processes underlying spelling achievement problems. The early identification of strengths and weaknesses of a child’s working memory and shifting capabilities, might help teachers to broaden their range of remedial intervention options to optimize school achievement.